Decisions on Estimation of Carbon Limits and Environmental Investment with Incomplete Information - Jian Pan; Yumei Jiang; Xiaran Zhang; Qingchun Meng (Discrete Dynamics in Nature and Society)
Due to the recent implementation of carbon limits and certain government delays in promulgating these limits, some firms are faced with incomplete information regarding their carbon limits, which hinders their ability to make environmental investments based on accurate information. This study aims to investigate firms’ optimal decisions regarding carbon limit estimations and environmental investment amounts when faced with incomplete information on carbon limits. In addition, it explores the impact of such uncertain regulations on firms’ environmental investments. These issues are progressively addressed through the establishment and resolution of a two-stage model. The research indicates that it is not always appropriate for firms to estimate carbon limits as the minimum value. While this strategy helps them better adapt to strict emission regulations, it involves substantial financial costs. The level of environmental investment is negatively influenced by estimated carbon limits, owing to the escalating marginal cost nature associated with reducing carbon emissions. However, the impact of carbon limit uncertainty on environmental investment is not constant. It can be positive, negative, or neutral depending on the firm’s trade-off between decision robustness and profit objectives. These findings provide insights into how firms in countries that have recently implemented carbon limits and delayed the disclosure of carbon limits can make environmental investments.